2003
DOI: 10.1002/mus.10527
|View full text |Cite
|
Sign up to set email alerts
|

Creatine monohydrate supplementation does not increase muscle strength, lean body mass, or muscle phosphocreatine in patients with myotonic dystrophy type 1

Abstract: Creatine monohydrate (CrM) supplementation may increase strength in some types of muscular dystrophy. A recent study in myotonic muscular dystrophy type 1 (DM1) did not find a significant treatment effect, but measurements of muscle phosphocreatine (PCr) were not performed. We completed a randomized, double-blind, cross-over trial using 34 genetically confirmed adult DM1 patients without significant cognitive impairment. Participants received CrM (5 g, approximately 0.074 g/kg daily) and a placebo for each 4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 52 publications
2
38
0
5
Order By: Relevance
“…46 Several studies have demonstrated the benefit from creatine monohydrate supplementation in mdx mice 15,26,36 and in patients with DMD. 25,47,52 Although increasing muscle creatine levels may be the mechanism behind a therapeutic effect, some studies have not measured muscle phosphocreatine and total creatine levels.…”
Section: Discussionmentioning
confidence: 99%
“…46 Several studies have demonstrated the benefit from creatine monohydrate supplementation in mdx mice 15,26,36 and in patients with DMD. 25,47,52 Although increasing muscle creatine levels may be the mechanism behind a therapeutic effect, some studies have not measured muscle phosphocreatine and total creatine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Les prélèvements sanguins effectués dans le but de mesurer ce paramètre sont très courants dans le suivi de ce type de maladie, notamment dans les différents types de dystrophies (Vassella et al, 1965;Goto et al, 1967;Rossi et al, 1990;Tarnopolsky et al, 2004). Lors d'une blessure ou d'une contraction contre résistance, des lésions microscopiques peuvent survenir et ces lésions provoquent l'élévation du taux plasmatique de CK.…”
Section: Créa Tine Kinaseunclassified
“…Randomized trials of testosterone and creatine failed to improve muscle strength in DM patients. [20][21][22][23] A pilot study reported that dehydroepiandrosterone (DHEA) improved strength in 11 DM patients, 24 and a phase II/III trial testing two doses of oral DHEA in DM patients has been completed (NCT00167609 at http://www. clinicaltrials.gov), although final results of this study had not been published as of June 2008.…”
Section: Reversal Of Muscle Wasting In Dm1: Igf-1/igfbp3mentioning
confidence: 99%